To gain face or not to lose face: the effect of face message frame on response to public service advertisements. Issue 8 (16th November 2020) - Wang, Hanwei; Fu, Hongyu; Wu, Yuanyuan
Abstract: The current research examines the effect of face message frame on consumers' response to public service advertisements (PSAs). Results of three experiments show that not-to-lose-face messages are more persuasive than to-gain-face messages in the contexts of both anti-drunk-driving PSAs (Experiment 1 and Experiment 3) and anti-drug PSAs (Experiment 2). Moreover, the framing effect is more pronounced for individuals whose interdependent self-construal is more accessible, but not for individuals whose independent self-construal is more accessible (Experiments 1, 2, and 3). The moderating effect of self-construal is significant when it is primed both through a task that is independent of the PSA (Experiment 1 and Experiment 2) and through the appeal type (Experiment 3). Further, the findings suggest that a congruency between a not-to-lose-face message and an interdependent appeal leads to more persuasiveness than other available conditions (Experiment 3). We also discuss contributions to theory and implications for advertising practice.